The meaning of dignity in care during the COVID-19 pandemic: a qualitative study in acute and intensive care - Loredana Buonaccorso; Ludovica De Panfilis; Harvey Max Chochinov; Gianfranco Martucci; Marco Massari; Monica Cocchi; Maria Chiara Bassi; Silvia Tanzi (BMC Palliative Care, 2023)
Abstract Background The pandemic Era has forced palliative care professionals to use a dignity-in-care approach in different settings from the classic ones of palliative care: acute and intensive care. We explored the meanings of dignity for patients, their family members, and clinicians who have experienced COVID-19 in the acute and intensive care setting. Methods A qualitative, prospective study by means of semi-structured interviews with patients hospitalized for COVID-19, family members, and clinicians who care for them. Findings Between March 2021 and October 2021, we interviewed 16 participants: five physicians, three nurses, and eight patients. None of the patients interviewed consented for family members to participate: they considered it important to protect them from bringing the painful memory back to the period of their hospitalization. Several concepts and themes arose from the interviews: humanity, reciprocity, connectedness, and relationship, as confirmed by the literature. Interestingly, both healthcare professionals and patients expressed the value of informing and being informed about clinical conditions and uncertainties to protect dignity. Conclusions Dignity should be enhanced by all healthcare professionals, not only those in palliative care or end-of-life but also in emergency departments.